Temperature extremes across elevation gradients: evidence from two German mountain observatories - Ionita, Monica; Cai, Di; Nagavciuc, Viorica (Frontiers in Earth Science, 2025)
Mountain regions are warming rapidly, yet long records across elevation are rare. This study presents the first comprehensive assessment of temperature extremes across an elevation gradient in the Bavarian Alps at two long-term observatories: Hohenpeißenberg (977 m a.s.l., 1781–2024) and Zugspitze (2,956 m a.s.l., 1901–2024). We find a pronounced warming at both sites, characterized by significant acceleration in recent decades. At Hohenpeißenberg, the annual mean temperature increased by approximately +0.07 °C dec−1 since 1781, intensifying to +0.51 °C dec−1 after 1980. At Zugspitze, the corresponding warming rates are +0.08 °C dec−1 since 1901 and +0.33 °C dec−1 post 1980. Warming trends exhibit strong seasonality: summer has warmed the fastest (e.g., +0.60 at Hohenpeißenberg and +0.62 °C dec−1 at Zugspitze, since the 1980s), whereas long-term winter warming was more modest (+0.07 °C dec−1 at Hohenpeißenberg since 1781, +0.11 °C dec−1 at Zugspitze since 1901) before sharply accelerating in recent decades. A weak elevation dependent warming (EDW) signal emerges in autumn, with high altitude temperatures increasing as rapidly as, or exceeding, those at lower elevation. In contrast, winter, spring, and summer warming magnitudes are greater at the lower elevation site, resulting in comparable or even stronger overall warming there. Temperature extremes have also changed markedly: cold extremes have declined significantly at both locations (e.g., the duration of cold spells has decreased by 16 days at Hohenpeißenberg and by 10 days at Zugspitze, over the period 1981–2024), while warm extremes exhibit a pronounced rise, especially in the Warm Spell Duration Index (WSDI), which has nearly doubled since the 1980s. Snow depth has declined across all seasons, with losses accelerating during the past 4 decades, particularly at Zugspitze. Interannual variations in warm and cold extremes are significantly modulated by leading Euro Atlantic modes of variability, including the North Atlantic Oscillation, the East Atlantic pattern, the Arctic Oscillation, and the Scandinavian pattern, whose influence peaks in winter. Collectively, these long-term records provide robust evidence of an anthropogenic influence on temperature extremes at the two long-term observatories, characterized by fewer and shorter cold spells, more frequent and persistent heatwaves, and declining snowpack. These findings highlight the urgent necessity of incorporating mountain specific observational evidence into regional climate adaptation and policy frameworks.